Students to the Heroes of the Artistic Work Non-Traditional that Teaches Critical Evaluation Lessons - Baltaeva Anadjan Tadjibaevna (International Journal on Orange Technologies, 2021)
This article focuses on the problem of shaping students ‘critical evaluation skills which evaluate literary heroes in literary work. The article reveals the features of the development of students' critical thinking in the process of studying literary work, emphasizes the technology of the formation of skills of critical evaluation literary work. Effective technical methods are methods that help to develop creative activity, analyze, observe, compare, and generalize and other skills.